LINGUOPRAGMATIC STUDY OF PHRASEOLOGICAL UNITS WITH A SOMATIC COMPONENT IN ENGLISH AND UZBEK LANGUAGES - Karimova , Ozodakhon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Every language is unique and one word or sign may mean differently each of them. So, this article is devoted to the research of one branch of linguistics – about phraseological units with somatic elements from the point of lingua-pragmatic aspect in both English and Uzbek languages. The purpose of article is to describe the way of phraseological units, indicating human’s interpretation and understanding of the world through the names of human body parts too. The choice of somatic phraseological units for research is explained not only by their wide range use in common life, but also by the fact that they are expressive, figurative, clearly reflect the peculiarities of the spiritual and material life of the person. Moreover, the background analysis of somatic phraseological units and lingua pragmatics are illustrated as well as meaning of the phraseological units with the component of somatisms are analyzed on a pragmatic basis. According to previous researches, most parts of the body and their nominations have several connotative symbolic meanings, arising from the basic meaning of the “human’s body part” based on the metonymic transference are studied. In order to explore some examples of somatic phraseological units, some methods are used such as illustration, observation and comparison. Many differences and similarities are revealed relying on lingua-pragmatic features in both languages because they differ from geneological and morphological perspectives. All examples of somatic phraseological units like idioms, proverbs and others given in the article are taken from paremiological and phraseological dictionaries as well as prominent novels in Uzbek and English.